Doses e parcelamento da adubação potássica na cultura da batata (Solanum tuberosum L.) - Job, André Luiz Gomes [UNESP] (2014)
With the use of more productive potato (Solanum tuberosum L.) cultivars, the plant’s demand for nutrients has possibly increased, raising the necessity of adjustments on fertilizer application. Potassium (K), which is extracted in high amounts, is one of the main nutrients absorbed by the plant. This compound is of pivotal importance to potato development, especially to increase its yield and to generate high quality tubers. Many producers are making use of fertilization without a proper technical recommendation. As K uptake by the plant is very high, low K rates and inadequate management can impair tuber yield, mainly in soil with low K availability. In this context, this study aimed to evaluate the effects of K fertilization rates and split application on nutrition and yield or potato crop, cv. Agata. For this, three field experiments was carried out on clay-textured soils with low (0.7 mmolc dm-3), medium (1.6 mmolc dm-3) and high (3.7 mmolc dm-3) exchangeable K concentration. These experiments was conducted under a randomized block design using a 3x2+1 factorial scheme, with four replications. The treatments consisted of three K rates (100, 200, and 400 kg ha-1 K2O), combined with two forms of split application (100 % at planting furrow or 50% at planting furrow + 50% at sidedressing, during hilling) and a control (without K application). Regardless of installments, increasing K rates showed an increase in K concentration in leaf of potato grown in soils with low, medium, and high K availability, but more markedly in soil with low availability. In soil with low concentration of exchangeable K, the application of K rate totally at planting furrow increased the concentration of K in the leaf than when split applied at planting and hilling. Regardless of the soil K availability, K fertilization reduced the concentrations of P, Ca, and Mg in leaf of potato crop and little influenced the ...